2020
DOI: 10.1038/s41598-020-60212-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle-miRNAs as liquid biopsy biomarkers for disease identification and prognosis in metastatic colorectal cancer patients

Abstract: Disseminated disease is present in ≈50% of colorectal cancer patients upon diagnosis, being responsible for most of cancer deaths. Addition of biological drugs, as Bevacizumab, to chemotherapy, has increased progression free survival and overall survival of metastatic colorectal cancer (mCRC) patients. However, these benefits have been only reported in a small proportion of patients. To date, there are not biomarkers that could explain the heterogeneity of this disease and would help in treatment selection. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 52 publications
2
65
0
Order By: Relevance
“…The miR-552 expression was also significantly up-regulated in various CRC cell lines including HCT116, HT-29, HCT-15, and HT-29 [21][22][23][24]. Consistent with this, miR-552 was also found to be up-regulated in the serum of CRC patients [25]. Comparing miR-552 expression in 158 pairs of colon cancer (CC) adenocarcinoma tissues with proficient DNA mismatch repair (pMMR) and adjacent tissues found that miR-552 expression was significantly associated with CC risk [20].…”
Section: The Clinical Significance Of Mir-552 In Human Cancersupporting
confidence: 71%
“…The miR-552 expression was also significantly up-regulated in various CRC cell lines including HCT116, HT-29, HCT-15, and HT-29 [21][22][23][24]. Consistent with this, miR-552 was also found to be up-regulated in the serum of CRC patients [25]. Comparing miR-552 expression in 158 pairs of colon cancer (CC) adenocarcinoma tissues with proficient DNA mismatch repair (pMMR) and adjacent tissues found that miR-552 expression was significantly associated with CC risk [20].…”
Section: The Clinical Significance Of Mir-552 In Human Cancersupporting
confidence: 71%
“…They can be loaded into exosomes or other extracellular vesicles (extracellular vesicle-encapsulated miRNA: EV-miRNA) or exist freely in the blood circulation (circulating miRNA). Among these two forms, EV-miRNA has several advantages over circulating miRNA: i) It can be specifically released for cell-to-cell communication, and ii) lipid membrane coverage protects miRNA from RNase degradation ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 Therefore, the increased amount of nucleosomerelated proteins identified in ovarian cancer patients in this study is likely to extend to other cancer types and NP classes, as a general reflection of increased histone levels commonly seen in cancer. [61][62][63][64] In recent years, other cell-free nucleic acids, such as miRNAs, have received growing interest as disease biomarkers 65 and although extensive characterisation of the NP corona total nucleic acid content was beyond the scope of this study, it remains an important avenue of future research. Blood-circulating RNA molecules are commonly complexed with proteins, including those forming the RNA-induced silencing complex (RISC).…”
Section: Discussionmentioning
confidence: 99%